The Practical Significance Of Improving Students' Musical Thinking And Perception Based On Traditional Singing Performance - Jumаyevа Mоhinisо Sа’dullаyevnа (Genius Publishing Group, 2025)
In the article, the artistic, creative-practical and amateur activities of the public; folk art of traditional material and non-material culture (folklore), folk music (musical folklore), folk theater (performance art), folk games (dance), puppetry, It talks about such creative types as gallows and wooden leg games (folk circus), folk visual and practical decorative arts, and technical and artistic hobby
Keywords: Traditional singing; stasis; solo performance; praise